Pengaruh Rasio Likuiditas, Solvabilitas,dan Profitabilitas Terhadap Harga Saham Pada Sektor Food And Beverages di Bursa Efek Indonesia - Grave, Anita De; Hasan, Syahril; Hariati, Hariati (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
Fundamental analysis is an approach most often used by investors to predict future stock price movements. An indicator that is often used by an investor in fundamental analysis is to look at the financial ratios in the financial statements issued by the company. This study aims to determine the effect of the Current Ratio, Debt To Equity Ratio, and Return On Equity on Stock Prices in the food and beverages sector on the Indonesia Stock Exchange. Sample determination was carried out using the Purposive Sampling method with research data obtained from financial statements for 5 years, namely the 2017-2021 period. The data analysis used is multiple linear regression analysis. The results of the t-test showed that the current ratio variable partially does not affect the stock price, the debt to equity ratio variable partially affects the stock price and the return on equity variable partially affects the stock price. The results of the F test, show that simultaneously the variable current ratio, debt to equity ratio, and return on equity simultaneously have an influence significant on stock prices.        Fundamental analysis is an approach most often used by investors to predict future stock price movements. An indicator that is often used by an investor in fundamental analysis is to look at the financial ratios in the financial statements issued by the company. This study aims to determine the effect of the Current Ratio, Debt To Equity Ratio, and Return On Equity on Stock Prices in the food and beverages sector on the Indonesia Stock Exchange. Sample determination was carried out using the Purposive Sampling method with research data obtained from financial statements for 5 years, namely the 2017-2021 period. The data analysis used is multiple linear regression analysis. The results of the t-test showed that the current ratio variable partially does not affect the stock price, the debt to equity ratio variable partially affects the stock price and the return on equity variable partially affects the stock price. The results of the F test, show that simultaneously the variable current ratio, debt to equity ratio, and return on equity simultaneously have an influence significant on stock prices.